2010
DOI: 10.1016/j.agee.2010.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Soil CO2 fluxes following tillage and rainfall events in a semiarid Mediterranean agroecosystem: Effects of tillage systems and nitrogen fertilization

Abstract: 1Management practices can influence soil CO 2 efflux in croplands. Under Mediterranean 2 conditions, soil CO 2 flux responds to tillage and precipitation events with different extent 3 and duration. CO 2 fluxes during these events may constitute a significant part of the annual 4 soil CO 2 emission. Further estimation of these events is required for estimation of the soil C 5 balance and modeling of C dynamics. The long-term effects of tillage practices (NT, no-6 tillage, MT, minimum tillage and CT, convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 46 publications
4
35
0
4
Order By: Relevance
“…Indeed, during that period, a total amount of rain water of 237 mm was recorded with maximum of 8 days between two consecutive rainfall events. This result corroborated with what Morell et al (2010) reported in a semiarid mediterranean agroecosystem. They reported that the CO 2 dependence on precipitation lasted for a period of time as long as the soil remained moist.…”
Section: Soil Respiration Rate and Its Seasonal Variationsupporting
confidence: 82%
“…Indeed, during that period, a total amount of rain water of 237 mm was recorded with maximum of 8 days between two consecutive rainfall events. This result corroborated with what Morell et al (2010) reported in a semiarid mediterranean agroecosystem. They reported that the CO 2 dependence on precipitation lasted for a period of time as long as the soil remained moist.…”
Section: Soil Respiration Rate and Its Seasonal Variationsupporting
confidence: 82%
“…Aumentos na FCO 2 induzido pelo preparo têm sido associados à intensidade do preparo do solo sendo um fator determinante da variabilidade do fluxo de CO 2 do solo em períodos curtos (La Scala et al, 2009;Morell et al, 2010). A atividade decompositora dos microrganismos também é intensificada imediatamente após o preparo do solo devido à exposição do carbono antes protegido no interior dos agregados, à maior oxigenação do solo e às temperaturas mais elevadas (Reicosky & Archer, 2007), ocasionando aumentos na emissão de CO 2 e decréscimo do carbono estocado no solo (Lal, 2009).…”
Section: Resultsunclassified
“…Panosso et al (2009a), em estudos conduzidos em área de cana queimada, no interior do Estado de São Paulo, também observaram aumento significativo na FCO 2 , após uma precipitação de 21 mm. Morell et al (2010), estudando o efeito no curto prazo de chuvas sobre o fluxo de CO 2 , em diferentes sistemas de manejo do solo, notaram que a FCO 2 foi significativamente maior nos sistemas de cultivo mínimo e plantio direto, quando comparados sistemas de preparo convencional do solo, dentro de um período de três dias depois da chuva.…”
Section: Resultsunclassified
“…Aumentos na FCO 2 induzido pelo preparo têm sido associados à intensidade desse, sendo fator determinante da variabilidade temporal do fluxo de CO 2 do solo em períodos curtos (La Scala et al, 2009;Morell et al, 2010). Além desses efeitos, o preparo deixa o solo suscetível ao processo de erosão, o que resulta, assim, em maior perda de C (Martínez-Mena et al, 2012).…”
Section: Resultsunclassified